Práticas baseadas em evidências científicas na atenção às mulheres assistidas no cenário de parto e nascimento - ROCHA, Karla Kelma Almeida (2021)
The moment of delivery is very significant in the life of the woman and her baby, being permeated with biological and psychological senses. For this reason, there is a proposal for the humanization of childbirth and birth that comes to recognize the obvious need to treat this moment with practices based on scientific evidence. The aim of the study was to analyze obstetric practices that are developed in a reference obstetric center in the state of Maranhão. Descriptive, exploratory study with a quantitative approach. Conducted through a questionnaire and checklist to evaluate good practices in childbirth and birth, involving 150 parturients from a university hospital in the city of São Luís - Maranhão / Brazil. Data collection was carried out from January 2020 to September 2020. For the presentation of the results, a descriptive analysis was used to characterize the sample and Fisher's Exact test to analyze the association between the independent variables and the dependent, adopting significance level of 5%. Most women were between 20 and 29 years old, brown color, with elementary education, with up to five prenatal consultations, primiparous, with at least one normal delivery, with no cesarean delivery and no abortion. The good practices of childbirth and birth offered for most parturients were: presence of a companion (96.0%), administration of 10 IU oxytocin after delivery (98.7%), verification of the mother's lochia (96.7%), breastfeeding in the first hour of life (94.7%), immediate skin-to-skin contact (90.7%), late cord clamping (81.3%), Apgar measurement (100.0%) and vitamin administration K in RN (100.0%). There was low adherence to the use of the partograph (34.0%), the good practice of prophylaxis of neonatal ophthalmia was not identified, the kristeller maneuver practice without scientific evidence continues to occur, practices such as episiotomy, amniotomy and administration of oxytocin in the work of births were identified and were not justified, most births were attended by medical professionals. A minority of parturient women benefited from assistance based on scientific evidence using good researched practices. The variables race / color, presence of the partogram, absence of stimulation of labor and delivery and delivery in a non-supine position were statistically significant with evidence-based assistance. It is concluded that practices based on scientific evidence were found, but practices supported by the technocratic model were also registered, requiring strategies to promote necessary changes in the obstetric model, so that there is greater adherence to the use of good practices as an innovative proposal in care obstetric in the context of the teaching hospital, which will overcome conservative practices.